Hindering factors of infant feeding practices among the mothers of mid western part of Nepal - Pyakurel, Manita; Bhandari, Sujeeta; Bhatta, Rishi (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: This study was aimed to provide baseline information on infant feeding knowledge, practices and hindering factors for proper feedings. Material and Methods: Among the 185 women with less than one year child coming on immunization clinic of health post of Chisapani Village Development Committee, infant feeding knowledge, practices were assessed by interviewing with semi structured questionnaire and focus group discussion. Results: Male children were more exclusively breastfed (33%) than female (27%) and exclusive breast feeding was lower in fifth and sixth month of age. All of them were aware that the baby should be fed only breast milk for 6 months, but the exclusive breastfeeding practice was found only in a very few mothers. Most of them had fed solid food after 3 months. Conclusion: Knowledge and practices on infant feeding do not go along despite the adequacy of knowledge due to the hindering factors like poverty, working mother, lack of support from family members and lack of support from the government infant. The gap between knowledge and practice can be lessened via informative activities on lactation management, endorsing policies and rights for mothers-infants relationship.